Dynamical characteristics of the COVID-19 epidemic: Estimation from cases in Colombia. (April 2021) - Diaz, Hernando; España, Guido; Castañeda, Nelson; Rodriguez, Laura; de la Hoz-Restrepo, Fernando
Highlights: In patients with coronavirus disease 2019 (COVID-19), the course of disease dynamics was found to be basically independent of age and sex. The probability of death, hospitalization, and ICU admission was found to be strongly dependent on age and sex. The parameters of all models have been estimated from a large sample. Abstract: Objective: To characterize the dynamics of the coronavirus disease 2019 (COVID-19) epidemic, for modeling purposes. Methods: Data from Colombian official case information were collated for a period of 5 months. Dynamical parameters of the disease spread were then estimated from the data. Probability distribution models were identified, representing the time from symptom onset to hospitalization, to intensive care unit (ICU) admission, and to death. Kaplan–Meier estimates were also computed for the probability of eventually requiring hospitalization, needing ICU attention, and dying from the disease (the case fatality ratio). Results: Probability distributions of the times and probabilities were computed for the population and for groups based on age and sex. The results showed that for the times that characterize the course of the disease for a given patient (time to hospitalization, ICU admission, or death), the variation from one age group to another was very small (around 10% of the fixed effect intercept) and the effect of sex was even smaller (around 1%). The course of the disease appeared to be very similar for all patients. On the other hand, the probability that a patient would advance from one stage of the disease to another (to hospitalization, ICU admission, or death) was heavily influenced by sex and age. The relative risk of death for male individuals was 1.7 times that of female individuals (based on 22 924 deaths). Conclusions: The times from one stage of the disease to another were almost independent of the major patient variables (sex, age). This was in stark contrast to the probabilities of progressing from one stage to another, which showed a strong dependence on age and sex. Data also showed that the length of hospital and ICU stays were almost independent of sex and age. The only factor that affected this length was the eventual outcome of the disease (survival or death); the time was significantly longer for surviving patients.